2011
DOI: 10.1101/pdb.prot067603
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Synaptic Vesicle Recycling by Staining and Destaining Vesicles with FM Dyes

Abstract: The synaptic vesicle is the essential organelle of the synapse. Many approaches for studying synaptic vesicle recycling have been devised, one of which, the styryl (FM) dye, is well suited for this purpose. FM dyes reversibly stain, but do not permeate, membranes; hence they can specifically label membrane-bound organelles. Their quantum yield is drastically higher when bound to membranes than when in aqueous solution. This protocol describes the imaging of synaptic vesicle recycling by staining and destaining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Similar results were observed using FM4-64 to label membrane ( Supplementary Fig. 7a ) 28 and Atto 488 to identify fusion modes (n = 75 spots, 6 cells, Supplementary Fig. 7b–d ).…”
Section: Resultssupporting
confidence: 79%
“…Similar results were observed using FM4-64 to label membrane ( Supplementary Fig. 7a ) 28 and Atto 488 to identify fusion modes (n = 75 spots, 6 cells, Supplementary Fig. 7b–d ).…”
Section: Resultssupporting
confidence: 79%
“…For the FM 1-43FX (Invitrogen) uptake assay, we used a modified version of a previously published protocol 72 . Neurons on sapphire disks were first incubated with 30 µM Pitstop 2 (Sigma) in physiological saline (1 mM Ca 2+ ) for 2 min.…”
Section: Fm Dye Uptake Imagingmentioning
confidence: 99%
“…7A). Synaptic activity was assessed using the fluorescent probe FM1-43, 32,33 by the ability of differentiated neurospheres to respond to depolarizing stimuli. Neurospheres at different stages of differentiation were loaded with FM1-43, and their destaining kinetics upon depolarization indicated that the same depolarizing stimuli led to a modest decrease in the fluorescence intensity of 7Diff and 21Diff neurospheres, when compared with neurospheres at the end of the differentiation process (18Mat), in which fluorescence dropped to less than half of its initial value (Fig.…”
Section: Neuronal Maturation and Synaptic Functionalitymentioning
confidence: 99%